مقارنة بين استخدام الأفلام الكرتونية والاغناء العربية لترقية قدرة الطلاب على الاستماع - Afifah, Nurul; Muhammad, Ismail; Fadhilah, Fadhilah (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2022)
The researcher choose this title because some of students at MTsS Darul Ulum thought if Arabic lesson is difficult and complicated. This because the teacher used old instructional media and made class atmosphere bored. So that makes students don’t like Arabic lesson. Expecially in listening, even though listening is a basic skill that students must have in learning a language. Therefore, researcher wants to use cartoon films and Arabic songs as a instructional media to improve student's listening skill. This study use an experimental method with a quasi-experimental research design. And the researcher took samples from class VIII3 and class VIII4 which amounted to 40 students, 20 students for the experimental cartoon film class and 20 students for the experimental Arabic song class. This study uses test instruments, namely pre-test and post-test, using descriptive statistical data analysis techniques, paired sample T-test, and independent sample T-test using the SPSS 25 program. The results of this research is the use of cartoon films media and Arabic songs are effective in improving student's listening skill. With the results of the paired sample T-test of cartoon film media of -7.958 (sig < 0.05) and the paired sample T-test of song media of -7.764 (sig < 0.05). And there are differences in the use of the two media with the results of the independent sample T-test (Sig 2 tailed) 0.134 (sig > 0.05) where the use of Arabic song media (86.00) is more effective than the use of cartoon film media (82.00) to improve student's listening skill.